A slow ride towards permanent residency: legal transitions and the working trajectories of Ukrainian migrants in Italy and Spain. Issue 13 (3rd October 2021) - Vianello, Francesca Alice; Finotelli, Claudia; Brey, Elisa
ABSTRACT: This article analyses the transition from temporary to permanent residency in Italy and Spain. Despite the growing number of permanent residents in Southern European countries, scholars have paid limited attention to the legal transitions that take place in migrants' lives after regularisation. We show that different regulations regarding permit renewals can account for qualitative differences in immigrants' permanent residency. The analysis focuses on legal transitions of  two groups of Ukrainian respondents in Italy and Spain. The significant presence of Ukrainian migrants in these two countries, together with the similarity of their legal migration patterns – from overstaying visas to obtaining long-term residency – makes Ukrainian immigration a particularly interesting case to study the hidden mechanisms and implications of legal transitions. The analysis presented here is based on 20 semi-structured interviews conducted in Italy and Spain and reveals differences between norms regarding the renewal of residency permits and their long-term implications for migrants' labour market participation. In Italy, restrictive renewal regulations and economic requirements contribute to entrapping Ukrainian immigrants in the live-in niche of care work, while occupational trajectories of Ukrainian migrants in Spain are more diverse due to less strict renewal regulations.